2015
DOI: 10.1246/cl.150381
|View full text |Cite
|
Sign up to set email alerts
|

Thermoresponsive Liquid Marbles Prepared with Low Melting Point Powder

Abstract: Thermoresponsive liquid marbles were prepared from water and 1-bromo-3-fluoro-4-iodobenzene (BFI) powder with a melting point of 46.5°C. The liquid marble can be floated on the surface of bulk water at room temperature, which is lower than the melting point of BFI. When the temperature of bulk water was increased above the melting point, the liquid marble disintegrated to leak the interior water to bulk water. Heating can be applied as a trigger of a chemical reaction between the interior reactant and another … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
17
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 19 publications
(4 reference statements)
0
17
0
Order By: Relevance
“…With these contaminants, the water surface tension decreased and the floating LM lost their integrity, revealing the water contamination without water sampling. On the same topic of responsive floating LM to external stimuli, Nakai et al reported a thermoresponsive LM that lost their integrity when the temperature increased and reached 46.5 °C . This temperature corresponded to the melting point of the material used in the LM coating.…”
Section: Liquid Marblesmentioning
confidence: 99%
“…With these contaminants, the water surface tension decreased and the floating LM lost their integrity, revealing the water contamination without water sampling. On the same topic of responsive floating LM to external stimuli, Nakai et al reported a thermoresponsive LM that lost their integrity when the temperature increased and reached 46.5 °C . This temperature corresponded to the melting point of the material used in the LM coating.…”
Section: Liquid Marblesmentioning
confidence: 99%
“…A liquid marble stabilized with BFI powder can float on bulk water. With increasing temperature of the bulk water, the liquid marble is disrupted at approximately 50 °C, which is close to the melting point . The BFI powder is adsorbed to the water droplet surface, and there is an air gap between the water in the liquid marble and the bulk water phase below the melting point.…”
Section: Stimuli‐responsive Liquid Marblesmentioning
confidence: 99%
“…14,18 Some liquid marbles can respond to various stimuli such as mechanical stress, 19 pH, 20 and temperature. 21,22 Deformed liquid marbles can be prepared by withdrawing the water content of the liquid marbles using a pipette. 23 It should be taken into consideration that the jamming effect enables the liquid marbles to deform to nonspherical shapes 24−26 as the monolayer of the hydrophobic sol−gel film mechanically transferred to the water droplet surface caused the jamming effect and unusual shapes of liquid marbles.…”
Section: ■ Introductionmentioning
confidence: 99%
“…To obtain nonspherical shapes of liquid marbles, acoustic levitation, electrical flow or magnetic field , were used, which enable temporary deformations of the liquid marbles’ shape, but it is self-reversed to the original spherical shape when the force is removed . Such strategies are used to manipulate the liquid marbles, for instance, electric or magnetic fields require adequate stimuli-responsive systems. , Some liquid marbles can respond to various stimuli such as mechanical stress, pH, and temperature. , Deformed liquid marbles can be prepared by withdrawing the water content of the liquid marbles using a pipette . It should be taken into consideration that the jamming effect enables the liquid marbles to deform to nonspherical shapes as the monolayer of the hydrophobic sol–gel film mechanically transferred to the water droplet surface caused the jamming effect and unusual shapes of liquid marbles. , Cylindrical shape oil marbles fabricated using modified fluorinated solid particles with omniphobic properties have been reported.…”
Section: Introductionmentioning
confidence: 99%